2008
DOI: 10.1680/coma.2008.161.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a warm-mix asphalt additive

Abstract: Although several warm-mix asphalt projects have been explored in the USA, Europe, and some countries in Asia, there is a need for the research to evaluate the applicability of warm-mix asphalt in Thailand. In this study, the fundamental properties of bitumen modified with one of the commonly used additives (Sasobit, a long-chain aliphatic hydrocarbon (LCAH)) were evaluated. The properties evaluated included the viscosity, rheological properties, rutting, and fatigue resistance. In addition, the compactability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 5 publications
1
17
1
1
Order By: Relevance
“…WMA technology can be used as a method of reducing the heat requirement for pavement operations while at the same time maintaining the integrity of the PMA binder. Several studies have been performed on the incorporation of wax additives into the PMA binder [11,5,15,14,17,16,20,19,21,32,13]. Most of the studies investigated the rheological properties of PMA binder by incorporating Sasobit into the binder.…”
Section: Introductionmentioning
confidence: 99%
“…WMA technology can be used as a method of reducing the heat requirement for pavement operations while at the same time maintaining the integrity of the PMA binder. Several studies have been performed on the incorporation of wax additives into the PMA binder [11,5,15,14,17,16,20,19,21,32,13]. Most of the studies investigated the rheological properties of PMA binder by incorporating Sasobit into the binder.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for adding Sasobit ® to asphalt binder is to decrease the mixing and compaction temperatures of asphalt mixes without sacrificing mix properties. Various studies on asphalt binder have shown that Sasobit ® increases the Superpave TM rutting factor (G*/sin d), zero shear viscosity (ZSV) and stiffness of asphalt binders [12][13][14][15][16] . Sasobit ® can be used in conjunction with other additive materials such as crumb rubber.…”
Section: Introductionmentioning
confidence: 99%
“…The longer chains help to keep the wax in solution, which reduces the viscosity of bitumen at typical asphalt production and compaction temperatures. Based on the literature, rates for Sasobit ® ranged from 1.0% to 4.0% by weight of the bitumen [31][32][33]. In this research, Sasobit ® content was chosen as 3.0%.…”
Section: Sasobitmentioning
confidence: 99%